Making an IMPACT: Empowering Student via Information Use - Flierl, Michael (Purdue University, 2016)
Presentation on Purdue's IMPACT program for the First Nations Knowledge Services without Borders Institute gathering at Maskwacis, Alberta in April, 2016.